Effect of three different set-up conditions on the propulsive force measures, reliability, and ecological validity during front crawl tethered-swimming - Joaquim Baratto de Azevedo O.* (2021)
© 2021 Cardiff Metropolitan University.This study analysed the effect of three set-up conditions on the propulsive force (PF) measures, test–retest reliability, and ecological validity during front crawl tethered-swimming (TS). Twenty-five (20.3 ± 3.7 years) swimmers performed TS in three conditions: Slp0 (0º of cable slope), Slp10 (10º of slope) and Slp20 (20º of slope), in two sessions. The second session included a 50-m performance and a questionnaire on the similarity of TS and free-swimming and overall comfort. Peak, mean force, impulse and force development rate, 50-m time and mean velocity, similarity scores and comfort were analysed. Effect of TS condition (p < 0.001) was observed for peak, mean force and force development rate. Regardless of the condition, reliability ranged from good to excellent (ICC = 0.79–0.95) and correlations with performance time (r≥-0.7) and mean velocity (r ≥ 0.63) were significant for all PF variables. The similarity between TS and free-swimming, and overall comfort as perceived by the swimmers, did not differ between conditions. Set-up condition influences the measures of PF in front-crawl TS. All conditions are reliable and present similar associations between PF and performance. Ecological validity indicators were near to the halfway point of the measurement scales independently of the condition.